A double Diels-Alder strategy towards the synthesis of Taxol analogues. - Parra, Stephanie Marie. (University of Ottawa (Canada), 2001)
TaxolRTM 1a, a very important drug used in cancer chemotherapy, has been synthesized by several groups. However these syntheses are long and there is still the need for a short and efficient route that would allow the production of this compound in larger amount. The route proposed by our group toward a simplified model compound 78 implied a double Diels-Alder strategy and started from readily available protected (L)-arabinose 118 or (D)-guluno-gamma-lactone 146. Conversion of 118 to 164, followed by Diels-Alder reaction led to the stereoselective construction of 165 . Deprotection of the isopropylidene acetal tether group and oxidative cleavage gave compounds 172a and 173a. We were able to ultimately get to compound 189. Despite precedents in the literature the second Diels-Alder cycloaddition required for the construction of rings A and B failed.
Keywords: Health Sciences, Pharmacology.